The decease of Edward I: Translation of codex BL Harley MS 2253, folios 73r-73v - Santos, Fernando Pereira dos [UNESP] (Univ Do Vale Do Rio Dos Sinos, 2018)
Among the events related to memory by men of learning in the Middle Ages, the demise of monarchs took its place in narratives concerned with historical record, either those of lay or clerical nature. In this work, we shall display an account of the death of Edward I (1239-1307), as we believe that its lines can be scrutinized by those interested in matters associated to the wars against the French and the Scots during his reign; furthermore, they can equally provide hints about the parameters of constitution of the royal figure and its desired audience in fourteenth-century England. For this reason, we seek to accomplish a double aim: firstly, on the basis of up-to-date studies regarding this specific writing, it shall be situated within its production context and, subsequently, we shall provide a complete translation of it into Brazilian Portuguese from a collation between folios 73r-73v, available at codex BL Harley MS 2253, and its two modern English editions.
Keywords: Harley MS 2253; Edward I; medieval England